Catwoman, soulstealer : the graphic novel - Simonson, Louise (DC Comics, 2021)
Selina Kyle returns to Gotham City as new socialite Holly Vanderhees, but she needs to outsmart rival Batwing to rise to the top of the city's criminal underbelly.